Steroidogenic and maturation-inducing potency of native gonadotropic hormones in female chub mackerel, Scomber japonicus - Ohga Hirofumi; Kaneko Kensuke; Shimizu Akio; Kitano Hajime; Selvaraj Sethu; Nyuji Mitsuo; Adachi Hayato; Yamaguchi Akihiko; Matsuyama Michiya (BMC, 2012)
Abstract Background The gonadotropins (GtHs), follicle-stimulating hormone (FSH) and luteinizing hormone (LH) are produced in the pituitary gland and regulates gametogenesis through production of gonadal steroids. However, respective roles of two GtHs in the teleosts are still incompletely characterized due to technical difficulties in the purification of native GtHs. Methods Native FSH and LH were purified from the pituitaries of adult chub mackerel, Scomber japonicus by anion-exchange chromatography and immunoblotting using specific antisera. The steroidogenic potency of the intact chub mackerel FSH (cmFSH) and LH (cmLH) were evaluated in mid- and late-vitellogenic stage follicles by measuring the level of gonadal steroids, estradiol-17beta (Ε2) and 17,20beta-dihydroxy-4-pregnen-3-one (17,20beta-P). In addition, we evaluated the maturation-inducing potency of the GtHs on same stage follicles. Results Both cmFSH and cmLH significantly stimulated E2 production in mid-vitellogenic stage follicles. In contrast, only LH significantly stimulated the production of 17,20beta-P in late-vitellogenic stage follicles. Similarly, cmLH induced final oocyte maturation (FOM) in late-vitellogenic stage follicles. Conclusions Present results indicate that both FSH and LH may regulate vitellogenic processes, whereas only LH initiates FOM in chub mackerel.